Spatio-Temporal Patterns of Saltwater Intrusion in A Narrow Meandering Channel - Jumain, Mazlin; Ibrahim, Zulkiflee; Makhtar, Md Ridzuan; Ishak, Roslee; Mohamed Rusli, Nurfarhain; Mat Salleh, Mohd Zulkhairi (International Journal of Integrated Engineering, 2022)
Saltwater intrusion has become a crucial issue for water resources management across the globe. Consequently, this issue leads to problems such as encroachment on water intake zone, loss of freshwater vegetation and also disturbance to aquatic life habitat. Undeniably climate change increases the saline water flow into the river system. The meandering rivers are common, and the hydraulics is more complex than straight rivers. An experimental hydraulic investigation was carried out in the Universiti Teknologi Malaysia to elucidate the hydrodynamic interactions between saline water and freshwater in a narrow meandering channel. The spatio-temporal salinity profiles along the river are discussed in this paper. The findings prevailed a typical characteristic of a salt-wedge estuary and indicated the processes of estuarine mixing. As the saltwater flows upstream, the salinity level drops due to the dilution process. Salinity levels and densimetric Froude number were mainly driven by freshwater discharge in the channel. A variation of dilution rate in a narrow meandering channel were up to 78.9% due to strong velocity forces produced by a high freshwater discharge. Furthermore, the flow resistance induced by the channel boundaries and meander planform itself influenced the salinity intrusion profiles along the channel.